E-commerce and its impact on wireless websites operational mechanisms. (18th July 2006) - Hsu, Li-Ling
The empirical study in this paper targeted leading Taiwanese software vendors. A total of 170 vendors of the Information Service Industry Association of Taiwan were selected as subjects of the analysis. The questionnaire was designed to investigate the impact of internal and external mechanisms on the goal setting of Small- and Medium-Sized Enterprises (SMEs) in e-commerce. Conclusions and managerial implications are provided that may assist SMEs in managing the m-commerce creation process.